Yogyakarta City Communication and Information Service's Public Relations Strategy in Realizing a Smart City Through Jogja Smart Service Application - Sitohang, Anastacia Margaretta; Setyaningsih, Rila; Awola, Eunike Dina (PT FORMOSA CENDEKIA GLOBAL, 2025)
In implementing the concept of a digital-based city, the Yogyakarta City Government through the Communication and Information Service has created an application, namely Jogja Smart Service. Public relations must create related strategies implementation of the smart city program so that it can reach smart city goals . In the research this , arises formulation problem that is How is the public relations strategy of the Yogyakarta City Communication and Information Service to realize a smart city through Jogja Smart Service application . In the thesis this , researcher use method study qualitative type descriptive . As for the research This use technique data collection observation , interviews , and documentation . The subjects of this study were the division of public information and communication and the division of information systems and statistics. In this study This use public relations strategy theory according to Cutlip, Center, and Broom. This theory explain about public relations strategy, namely defining problems, planning and programming , taking action and communication , and evaluate the program. From the data found , researchers find a number of findings namely at the stage defining the problem of the Yogyakarta City Communication and Information Service do activity special For analyze problem but utilise technology that can give convenience for community , planning and programming Yogyakarta City Communications and Information Service has created plan in form application that summarizes all service Yogyakarta City Government , carries out action and communication that is Yogyakarta City Communications and Information Service is carrying out socialization in a way direct to community and use social media Instagram and YouTube to introduce Features Jogja Smart Service application , and do evaluation that is Yogyakarta City Communication and Information Service only do evaluation with internal and inviting other OPDs to see development Jogja Smart Service application .